Characterization of Gold Coating on Nanostructured CR39 Polymer as SERS Sensor - Rana M. Taha and Hussein A. Jawad, (Iraqi Journal of Laser, 2018)
Abstract: The development of highly sensitive sensors has become an efficient field of research. In this work, an ArF Excimer laser of 193 nm with a maximum pulse energy of 275 mJ, 15 ns pulse duration and a repetition rate of 1 Hz is utilized to form a Laser Induced Periodic Surface Structures (LIPSS) of three different morphologies (nanochains, contours, grooves) on surface of CR39 polymer at a fluence range above the ablation threshold (250 mJ/cm2). The laser ablated polymer surface is then Surface Enhanced Raman Scattering (SERS) activated by deposition of a gold layer of 30 nm thickness. The capability of the produced substrate for surface enhanced Raman scattering is evaluated through thiophenol as an analyte molecule. It is observed that the Laser Induced Periodic Surface Structures of grooves like nanostructures coated with 30 nm gold layer gives a best enhancement factor in the range from 0.9*108 to 2*108 which is suitable for a single- molecule sensitivity.